2021
DOI: 10.3390/rs13214303
|View full text |Cite
|
Sign up to set email alerts
|

Improved Filtering of ICESat-2 Lidar Data for Nearshore Bathymetry Estimation Using Sentinel-2 Imagery

Abstract: The accurate estimation of nearshore bathymetry is necessary for multiple aspects of coastal research and practices. The traditional shipborne single-beam/multi-beam echo sounders and Airborne Lidar bathymetry (ALB) have a high cost, are inefficient, and have sparse coverage. The Satellite-derived bathymetry (SDB) method has been proven to be a promising tool in obtaining bathymetric data in shallow water. However, current empirical SDB methods for multispectral imagery data usually rely on in situ depths as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Moreover, the validation results of SDB models using blue and green bands of Zhuhai-1 (ZBR2, 9, ZLB3, 9, and ZLB3, 9, 12) image showed a similar accuracy to that of Sentinel-2 image (SBR2, 3, SLB2, 3, and SLB2, 3, 4), which further confirmed The most commonly used band-combination strategy for shallow-water bathymetry may be the employment of blue and green bands, of which principle and potential have been revealed in previous research [52]. The blue and green bands of Sentinel-2 image have been widely and successfully used for shallow-water bathymetry [53]. In this study, relative high correlations were observed for the blue and green bands between Zhuhai-1 and Sentinel-2 (R 2 > 0.7, Figure 13).…”
Section: Comparison Of Bathymetric Capability Between Zhuhai-1 and Se...supporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the validation results of SDB models using blue and green bands of Zhuhai-1 (ZBR2, 9, ZLB3, 9, and ZLB3, 9, 12) image showed a similar accuracy to that of Sentinel-2 image (SBR2, 3, SLB2, 3, and SLB2, 3, 4), which further confirmed The most commonly used band-combination strategy for shallow-water bathymetry may be the employment of blue and green bands, of which principle and potential have been revealed in previous research [52]. The blue and green bands of Sentinel-2 image have been widely and successfully used for shallow-water bathymetry [53]. In this study, relative high correlations were observed for the blue and green bands between Zhuhai-1 and Sentinel-2 (R 2 > 0.7, Figure 13).…”
Section: Comparison Of Bathymetric Capability Between Zhuhai-1 and Se...supporting
confidence: 78%
“…The most commonly used band-combination strategy for shallow-water bathymetry may be the employment of blue and green bands, of which principle and potential have been revealed in previous research [52]. The blue and green bands of Sentinel-2 image have been widely and successfully used for shallow-water bathymetry [53]. In this study, relative high correlations were observed for the blue and green bands between Zhuhai-1 and Sentinel-2 (R 2 > 0.7, Figure 13).…”
Section: Comparison Of Bathymetric Capability Between Zhuhai-1 and Se...mentioning
confidence: 99%
“…Despite the accuracy of existing DBSCAN methods, it is still very difficult to determine the values of key algorithm parameters due to the number of raw photons and the complexity of the underwater terrain. In our previous study, we proposed an adaptive ellipse DBSCAN (AE-DBSCAN) algorithm for ICESat-2 photon data processing (Xie et al, 2021). AE-DBSCAN can calculate the optimal detection parameters by adaptive iteration.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these assumptions and considering the increasing need for continuous and large-scale monitoring of environmental evolution along coastal belts, remote sensing (RS) offers a practical alternative for the extraction of depth information and the achievement of fast, repetitive, and low-cost bathymetry. In particular, the application of satellite-derived bathymetry (SDB) has achieved widespread adoption [10][11][12][13][14][15][16][17][18][19][20][21][22]. To this end, the availability of Copernicus (https://www.copernicus.eu/en, accessed on 30 May 2023) open data and their integration with other spatial data, which has opened up new horizons for downstream satellite applications [23], offers important benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the SDB literature mentions two approaches: (i) the physically based one, which relies on the physics of the exponential attenuation of light with depth in the water column and its reflection from either the water column or the seabed [17,18]; (ii) the empirical approach, without considering spectral, radiometric, and environmental parameters. The latter derives seabed estimates based on the statistical similarity of spectral signatures defined within different classes by defining specific training vectors [19,20] and relies on bathymetric data measured in situ to calibrate satellite images and validate the outcomes; hence, the SDB depth accuracy is limited in the absence of in situ depths [21].…”
Section: Introductionmentioning
confidence: 99%